Rancang Bangun Smart Learning Elektronika Berbasis Android pada Program Studi Pendidikan Teknik Elektro - Mursyidin Mursyidin; Sri Wahyuni; Junaidi (Jurnal Ilmiah Informatika, 2022)
The lack of variety of learning resources can be an obstacle in the teaching and learning process, learning that is only guided by the teacher and the material given by each meeting will greatly affect the success of learning. This electronic smart learning application is designed to make it easier for students to deepen their understanding of basic electronic lecture materials. This android-based electronic smart learning application was developed using research and development (R&D) methods and using the ADDIE development model. The results of the material expert validation showed that the application was worthy of use as a learning medium with an average score of 85% with "very suitable" criteria, and the media expert validation results obtained an average score of 82.22% with the "very suitable" criteria.